The Effectiffeness of The Process-Based Skills Approach of Lesson Study Toward Achievement In Biology of Vocational School Students - Faizah Firdaus; Suratno Suratno; Kamalia Fikri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Theory and practice are the one-entity that must be mastered in studying biology. Facts show that biological knowledge is not accompanied by practice of such science so that it focuses on theory. For that, it takes a learning approach that develops the skills to process knowledge acquisition that is the process skill approach. In addition to implementation of the strategies used, success in teaching and learning can not be separated from the teacher's efforts. Lesson Study is one that can be used as a method for teachers to exchange ideas in the preparation and development of biology learning plan. The purpose of this research is to know the effectiveness of process approach based on Lesson Study on Biology student learning outcomes. This research type is quasi experimental by applying approach of process skill base on Lesson Study in experiment class and conventional learning model, that is lecturing and question and answer in control class. Results of the analysis using the effectiveness test using gain score. Average gain score of the experimental class is greater than the average gain score control class which means that learning using the approach of Lesson Study based process skills is more effective than conventional learning. Result of the affective value analysis using independent t-test shows (sig = 0,000 <0,05) so that based on the same variance assumption, the two classes have significant affective value difference or in other words there is influence of different treatment to student affective value..